Determination of radon concentrations and physicochemical parameters of non-alcoholic carbonated beverages consumed in Türkiye and assessment of radiological health risk - Turhan, Şeref; Sultan, Dalal A O; Altuner, Ergin M; Kurnaz, Aslı; Bakır, Temel K; Altamemi, Raghda A A (Informa UK Limited, 2024)
The strategy for controlling the existence of radionuclides in drinking water depends upon an individual dose criterion (IDC) of 0.1 mSv/y, which represents a very low level of risk that is not expected to cause any identified adverse health effects. Radon gas, considered a carcinogenic radionuclide, can dissolve and accumulate in drinking water. Non-alcoholic carbonated beverages (NACBs), which mainly contain drinking water, phosphoric acid, citric acid, caffeine, and sugar, represent one of the most consumed groups worldwide and in Türkiye. In this study, the radon activity concentration and some physicochemical characteristics of 45 NACB samples from 24 most preferred commercial brands in Türkiye were determined to assess the radiological health risk associated with the ingestion of these samples. Radon activity concentrations measured in NACB samples using the AlphaGUARD radon analyzer ranged from 22.8 ± 0.7 to 54.9 ± 1.7 mBq/L. The pH, conductivity, total dissolved solids, and brix values in NACB samples ranged from 2.31 to 7.29, 401 to 3281 μSv/cm, 355 to 2453 mg/L, and 0.10 to 12.95%, respectively. Total (ingestion and inhalation) annual effective doses and the corresponding excess lifetime cancer risks estimated for adults to assess the radiological health risk are significantly below the IDC and advised safety limit (10-3), respectively.
Keywords: Turkey; Radon; Humans; Carbonated Beverages; Risk Assessment